Thrombin treatment induces rapid changes in tyrosine phosphorylation in platelets. - Golden, A (1989)
We previously demonstrated that platelets express high levels of the tyrosine protein kinase pp60c-src. By a quantitative immunoblot assay, it is shown in this report that pp60c-src represents 0.2-0.4% of total platelet protein. The expression of high levels of pp60c-src in platelets correlated with high levels of total cell phosphotyrosine. Unstimulated platelets were shown to possess numerous phosphotyrosine-containing proteins by immunoblot analysis using antibodies that specifically recognize phosphotyrosine residues. To examine whether the pattern of phosphotyrosine-containing proteins changes upon platelet activation, lysates from thrombin- and phorbol ester-treated platelets were subjected to immunoblot analysis. Novel phosphotyrosine-containing proteins were detected within seconds following platelet stimulation. These results suggest that tyrosine phosphorylation, perhaps mediated by pp60c-src, may be involved in events associated with platelet activation.